A new species of Pliosaurus (Sauropterygia, Plesiosauria) from the upper Jurassic of northwestern Patagonia, Argentina - Brandoni, Zulma Nelida (2014)
Pliosaurus patagonicus sp. nov., from the middle Tithonian, Vaca Muerta Formation, Neuquén Province, Argentina, is described on an autapomorphic trait –i.e., the distance between the posterior functional alveolus and coronoid eminence (300 mm) equivalent to the last fourteen alveoli– and a unique combination of characters: short and robust mandibular symphysis with six pairs of functional alveoli; in lateral view the dorsoventral height is almost constant along the symphysis; low coronoid eminence and mandibular rami almost straight. As in other species of Pliosaurus genus the new taxon has trihedral teeth but the typical lateral expansion of the mandibular symphysis is missing. This new record reinforces the hypothesis of a trend toward the shortening of the mandibular symphysis observed in late Kimmeridgian–Tithonian species from the northern hemisphere. The presence of the macropredator Pliosaurus patagonicus sp. nov. in a protected marine environment close to the coast may be interpreted as the result of predatory and/or reproductive behaviors.